Systematic review and meta-analysis of belatacept versus calcineurin inhibitors on risk of post-transplant diabetes mellitus in kidney transplant recipients - Wang, Xuchuan; Song, Dandan; Hou, Shufu; Liu, Aiju; Gao, Jing; Liu, Lei (Frontiers in Immunology, 2026)
BackgroundThe novel immunosuppressant belatacept demonstrates a unique mechanism of action that significantly improves renal function and reduces metabolic complications. However, systematic evidence comparing the risk of post-transplant diabetes mellitus (PTDM) and overall safety profiles between belatacept-based regimens and calcineurin inhibitor (CNI)-based protocols remains limited. This meta-analysis aims to synthesize high-quality evidence to determine the comparative efficacy of these two regimens in PTDM prevention and safety outcomes, thereby providing robust guidance for clinical decision-making.MethodsWe systematically searched PubMed, Cochrane Library, CNKI, and EMBASE for studies published until November 30, 2024, comparing belatacept versus calcineurin inhibitors (CNIs) regarding PTDM risk in kidney transplant recipients. The primary outcome was PTDM incidence. Following data extraction and quality assessment, we performed pairwise meta-analyses to compare PTDM risk between belatacept (either less intensive(LI) or more intensive (MI) regimen) and CNIs. Bayesian network meta-analysis (WinBUGS 1.4.3) was then conducted for indirect comparison between belatacept LI and MI regimens.ResultsThe initial search yielded 3,206 records. After deduplication, title/abstract screening, and full-text evaluation, 6 studies involving 1,737 kidney transplant recipients were included in the final analysis. Compared with CNIs, belatacept demonstrated significant reductions in PTDM risk for both the LI (RR = 0.65, 95% CI 0.52-0.81, p<0.001; I²=30%) and MI (RR = 0.65, 95% CI 0.52-0.81, p<0.001; I²=30%) regimens. Bayesian network meta-analysis revealed no statistically significant difference between the LI and MI regimens.ConclusionsThis meta-analysis demonstrates that belatacept significantly reduces PTDM risk compared to CNIs, a finding consistent with previous studies. Notably, both LI and MI dosing regimens showed protective effects, suggesting that even low-intensity belatacept therapy could serve as a viable alternative to CNIs, particularly for patients requiring reduced immunosuppressive toxicity.Systematic review registrationhttps://inplasy.com/, identifier INPLASY202540041.